Impact of manager characteristics and organizations on controlling practices (Research, Society and Development, 2020)
The objective is to analyze how organizational resources that influence the applicability of driver practices. It is a descriptive, quantitative and survey type survey. A sample comprised 108 companies, small, medium and large, in the commercial, industrial and service sectors. For statistical analysis, Kruskal Wallis and Chi Square tests were applied. The findings suggested for resources such as tax regime, legal configuration, company size and academic training, define the usage and driver parameters in companies. It is assumed that the study of academic assistants and managers understands as reasons that lead as activities to use limited management resources. A driver created on an important theme, especially, because it serves to support and guide as printed decisions.